Comportamento reológico de um solo argiloso laterítico compactad - Mello, Leonardo Brizolla de (2022)
This research aims to evaluate possible relations between rheological tests and those carried out on resiliente modulus tests, aimed at understanding the performance of compacted earth materials in pavements. Samples dented from a lateritic clayey soil were selected for the collection, with previous chemical, physical and mechanical characterization, from the city of Cruz Alta (RS) and with wide application in road subgrade structures. The rheological performance was weighted in a total of ninety samples divided between the amplitude sweep test (AS) and frequency sweep test (FS). Specimens molded in three different compaction energies (normal, intermediate, and modified), and five standard moisture variations around the optimum content of each energy, characterized by Wót-4%, Wót-2%, Wót, Wót+2 %, and Wót+4% were analyzed. The proposal to evaluate compacted materials by amplitude sweep tests made it possible to understand that the ideal for compacted soils is the molding of specimens in the torsion geometry of bars. This test also allows us to infer that the intervals of the linear viscoelastic limit (VEL) of the CA soil can reach a shear strain common to all samples equal to 0.005%. The AS also revealed that for very low shear strain, there is an inefficiency of reading by the rheometer. At values that exceed the VEL, the elements show a drop in stiffness due to the increase in non-recoverable plastic deformations, which come to dominate their behavior and subsequently lead to brittle failure at δ below seven degrees. FS assays worked with samples at VEL. These revealed that soils are viscoelastic materials even at lower frequencies. From this, it is verified how susceptible the samples are to frequency and humidity variation, which need to be considered in pavement design. From this test, master curves, called isogrócopes, were plotted, considering the partial overlapping frequency - humidity, with |G*| as a function of the frequency translated on the x-axis of the graphs by shift factor, which allowed estimating the resilient behavior of the material in a frequency of 10Hz. This translation also made it possible to identify that the susceptibility to moisture variation is very similar between the different compaction energies. With the conversion of the resilient modules into shear modules, it appears that the mathematical model of Svenson, for not considering the action of confining stresses, proved to be effective when compared to the Universal (model that best represented the resilient behavior of the soil) for the intermediate energy and modified. Finally, it was understood that, despite the limitations given by the different characteristics of the MR and FS tests, such as the different ways of applying the loads and the existence of confining stresses in the rheological tests, the relationships proved to be promising for the expeditious investigation of the behavior regarding the rigidity of compacted soils intended for paving.